A versatile functionalized ionic liquid to boost the solution-mediated performances of lithium-oxygen batteries - Zhang, Jinqiang; Sun, Bing; Zhao, Yufei; Tkacheva, Anastasia; Liu, Zhenjie; Yan, Kang; Guo, Xin; McDonagh, Andrew M.; Shanmukaraj, Devaraj; Wang, Chengyin; Rojo, Teofilo; Armand, Michel; et al. (Nature communications, 2019)
Due to the high theoretical specific energy, the lithium–oxygen battery has been heralded as a promising energy storage system for applications such as electric vehicles. However, its large over-potentials during discharge–charge cycling lead to the formation of side-products, and short cycle life. Herein, we report an ionic liquid bearing the redox active 2,2,6,6-tetramethyl-1-piperidinyloxy moiety, which serves multiple functions as redox mediator, oxygen shuttle, lithium anode protector, as well as electrolyte solvent. The additive contributes a 33-fold increase of the discharge capacity in comparison to a pure ether-based electrolyte and lowers the over-potential to an exceptionally low value of 0.9 V. Meanwhile, its molecule facilitates smooth lithium plating/stripping, and promotes the formation of a stable solid electrolyte interface to suppress side-reactions. Moreover, the proportion of ionic liquid in the electrolyte influences the reaction mechanism, and a high proportion leads to the formation of amorphous lithium peroxide and a long cycling life (> 200 cycles). In particular, it enables an outstanding electrochemical performance when operated in air. Li-O 2 batteries are promising candidates for the next generation of rechargeable batteries, but the side reactions and poor cycling stability limit their applications. Here, the authors show a versatile ionic liquid with functional groups that can address both issues for cells operated in oxygen and air.